Double fillet lap of laser welding of thin sheet AZ31B Mg alloy - M., Ishak; M. N. M., Salleh (Institute of Physics Publishing, 2018)
In this paper, we describe the experimental laser welding of thin sheet AZ31B using double fillet lap joint method. Laser welding is capable of producing high quality weld seams especially for small weld bead on thin sheet product. In this experiment, both edges for upper and lower sheets were subjected to the laser beam from the pulse wave (PW) mode of fiber laser. Welded sample were tested their joint strength by tensile-shear strength method and the fracture loads were studied. Strength for all welded samples were investigated and the effect of laser parameters on the joint strength and appearances were studied. Pulsed energy (EP) from laser process give higher effect on joint strength compared to the welding speed (WS) and angle of irradiation (AOI). Highest joint strength was possessed by sample with high EP with the same value of WS and AOI. The strength was low due to the crack defect at the centre of weld region.